Analysis of the competitiveness of rice farming and its implications on Input-Output price policy scenario of rice in Jambi Province - Indonesia - Murdy, Saad; Nainggolan, Saidin; Rezeki. R Sihombing, Sri (Jurnal Paradigma Ekonomika, 2021)
The research objectives are: 1). to analyze the levels of private and social profitability of rice farming, 2). to analyze comparative advantage and competitive advantage rice farming, 3).to analyze the impact of input = output price policy on the competitiveness of rice farming. The study was conducted in rice production centers in the province of Jambi, named Kerinci, Sarolangun, Bungo and Tanjung Jabung Barat determined purposively. The sample size was 314 farmers with methods of Simple Random Sampling. Methods of data analysis used the Policy Analysis Matrix approach (PAM). The results showed that rice farming has high competitiveness. The increase in production input prices does not affect the declining competitiveness. The increase in the price of rice paddy resulted in more and more advantages. Â